2013
DOI: 10.4014/jmb.1308.08015
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Halophilic Archaea in Fermented Foods and Human Intestines and Their Application

Abstract: Archaea are prokaryotic organisms distinct from bacteria in the structural and molecular biological sense, and these microorganisms are known to thrive mostly at extreme environments. In particular, most studies on halophilic archaea have been focused on environmental and ecological researches. However, new species of halophilic archaea are being isolated and identified from high salt-fermented foods consumed by humans, and it has been found that various types of halophilic archaea exist in food products by cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 63 publications
0
37
0
5
Order By: Relevance
“…Recently, Lee (2013) reported the use of halophilic bacteria for industrial food application. The inoculum of halophilic bacteria as starter culture into salted fishes might shorten the ripening period of salted anchovies and might improve the safety and sensory quality of the final products due to decrease of the levels of Enterobacteriaceae and staphylococci.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Lee (2013) reported the use of halophilic bacteria for industrial food application. The inoculum of halophilic bacteria as starter culture into salted fishes might shorten the ripening period of salted anchovies and might improve the safety and sensory quality of the final products due to decrease of the levels of Enterobacteriaceae and staphylococci.…”
Section: Discussionmentioning
confidence: 99%
“…1441/2007EC No. 1019/2013FDA, 1998). The histamine limits for ripened brined and/or salted fishery products have been established at 400 and 500 ppm in Europe and USA, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been found that halophilic archaea are able to produce extracellular serine proteases which are active in high salinity. The use of these proteases was implemented in the food industry to achieve the specific flavor of fish sauce, and fermented anchovy (Lee 2013).…”
Section: Enzymesmentioning
confidence: 99%
“…This does not mean that culture-dependent techniques are overlooked. Their potential is still utilised to understand the functioning of ecosystems and the components they consist of (Lee 2013;Oren 2015).…”
mentioning
confidence: 99%